2019
DOI: 10.1103/physrevc.99.054905
|View full text |Cite
|
Sign up to set email alerts
|

Testing production scenarios for (anti-)(hyper-)nuclei and exotica at energies available at the CERN Large Hadron Collider

Abstract: We present a detailed comparison of coalescence and thermal-statistical models for the production of (anti-)(hyper-)nuclei in high-energy collisions. For the first time, such a study is carried out as a function of the size of the object relative to the size of the particle emitting source. Our study reveals large differences between the two scenarios for the production of objects with extended wavefunctions. While both models give similar predictions and show similar agreement with experimental data for (anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 61 publications
3
80
0
Order By: Relevance
“…Common approaches used to describe the production of these loosely-bound objects include the thermal-statistical approach [4][5][6][7][8] and the coalescence model [9][10][11][12], a determination of the production mechanism is of great interest [see, e.g., Refs. [13][14][15][16][17][18][19][20] for recent results within these two approaches]. The measured yields have been observed to agree remarkably well with a thermal model calculation at a temperature T ch 155 MeV of the conventional chemical freeze-out of hadrons [21][22][23], while the available transverse momentum spectra of both nuclei and stable hadrons are characterized by a lower kinetic freeze-out temperature T kin 100 − 115 MeV [1].…”
supporting
confidence: 56%
“…Common approaches used to describe the production of these loosely-bound objects include the thermal-statistical approach [4][5][6][7][8] and the coalescence model [9][10][11][12], a determination of the production mechanism is of great interest [see, e.g., Refs. [13][14][15][16][17][18][19][20] for recent results within these two approaches]. The measured yields have been observed to agree remarkably well with a thermal model calculation at a temperature T ch 155 MeV of the conventional chemical freeze-out of hadrons [21][22][23], while the available transverse momentum spectra of both nuclei and stable hadrons are characterized by a lower kinetic freeze-out temperature T kin 100 − 115 MeV [1].…”
supporting
confidence: 56%
“…However, recent studies [5] have shown a sizable difference for the B A parameter as a function of the size of the particle emitting source between predictions by the SHM with kinetic freeze-out conditions from a simple hydrodynamical model and the coalescence model. Here, information from Hanbury Brown-Twiss (HBT) correlations is used to determine the source size.…”
Section: Introductionmentioning
confidence: 93%
“…is the invariant yield of protons, which is expected to be identical to that of neutrons at midrapidity and LHC energies [5]. Here, the coalescence probability is given by the parameter B A .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the LHC, the ALICE Collaboration has studiedp,d, 3H e, and 4H e production in pp, p-Pb, and Pb-Pb collisions at center-of-mass energies per nucleon pair from 0.9 to 13 TeV [26][27][28][29][30][31][32], and the yields obtained for A ≥ 2 have been interpreted by means of coalescence or statistical hadronization models [33][34][35][36]. The LHC measurements combined with different coalescence models have been employed to estimate the antideuteron and antihelium flux from cosmic-ray interactions measurable by the AMS-02 and GAPS experiments [15,[37][38][39].…”
mentioning
confidence: 99%